Faktor-faktor yang Berhubungan dengan Kekambuhan Orang dengan Skizofrenia yang Berobat di Poli-Klinik Rumah Sakit Jiwa Prof. Dr. Muhammad Ildrem Medan Tahun 2021 - Arif Irpan Tanjung; Meri Neherta; Rika Sarfika (Universitas Batanghari Jambi, 2022)
Relapse in People with Schizophrenia is a problem that often occurs in People with Schizophrenia. These recurrences occur due to various things that are directly related to the patient. Relapse in People with Schizophrenia is a problem that must be considered, because the relapse can be minimized by preventing the cause of the relapse. Many factors that influence the occurrence of relapse in schizophrenia patients can be detrimental to the family, society and the environment and themselves. These causes include medication adherence, support from health workers, family support and genetic history of the patient himself. The purpose of this study was to determine the factors associated with the recurrence of people with schizophrenia. The type of research used is a quantitative type of correlation research with a cross-sectional design approach. The research sample was 266 people, using the continuous sampling technique. The research instrument used a questionnaire. Data analysis using bivariate test with chi square and multivariate using logistic regression. The results of the study obtained the significance value of the relationship between various recurrence factors, including: medication adherence sig. 0.000 <0.05, health worker support sig. 0.006<0.05, family support sig. 0.000 <0.05, and genetic history with sig. 0.000<0.05. The conclusion of the study is that there is a relationship between medication adherence, support from health workers, family support and genetic history with recurrence of people with schizophrenia. It is hoped that the hospital and the family will pay attention to the factors associated with the recurrence, so that the recurrence of people with schizophrenia can be minimized.